A) 648-34*x=444
-34*x=-204
x=6
B)1482:x+23=80
1482:x=57
x=26
a) 648 - 34 . x = 444
34 . x = 648 - 444
34 . x = 204
x = 204 : 34
x = 6
b) 1482 : x + 23 = 80
1482 : x = 80 - 23
1482 : x = 57
x = 1482 : 57
x = 26
a ) 648 - 34 * x = 444
34 * x = 648 - 444
34 * x = 204
x = 204 : 34
x = 6
b ) 1482 : x + 23 = 80
1482 : x= 80 - 23
1482 : x = 57
x = 1482 : 57
x = 26
a,648-34.x=444
34.x=204
x=204:34
x=6
Vậy x=6
b,1482:x+23=80
1482:x=57
x=26
Vậy x=26
a) 648 - 34 . x = 444
34 . x = 648 - 444
34 . x = 204
x = 204 : 34
x = 6
b) 1482 : x + 23 = 80
1482 : x = 80 - 23
1482 : x = 57
x = 1482 : 57
x = 26
a) 648 - 34 . x = 444 34 .
x = 648 - 444
34 . x = 204
x = 204 : 34
x = 6
b) 1482 : x + 23 = 80
1482 : x = 80 - 23
1482 : x = 57
x = 1482 : 57
x = 26